Exposure to COVID-19 is associated with increased altruism, particularly at the local level - Gianluca Grimalda; Nancy R. Buchan; Orgul G. Ozturk; Adriana C. Pinate; Giulia Urso; Marilynn B. Brewer (Scientific Reports, 2021)
Theory posits that situations of existential threat will enhance prosociality in general and particularly toward others perceived as belonging to the same group as the individual (parochial altruism). Yet, the global character of the COVID-19 pandemic may blur boundaries between ingroups and outgroups and engage altruism at a broader level. In an online experiment, participants from the U.S. and Italy chose whether to allocate a monetary bonus to a charity active in COVID-19 relief efforts at the local, national, or international level. The purpose was to address two important questions about charitable giving in this context: first, what influences the propensity to give, and second, how is charitable giving distributed across different levels of collective welfare? We found that personal exposure to COVID-19 increased donations relative to those not exposed, even as levels of environmental exposure (numbers of cases locally) had no effect. With respect to targets of giving, we found that donors predominantly benefitted the local level; donations toward country and world levels were half as large. Social identity was found to influence charity choice in both countries, although an experimental manipulation of identity salience did not have any direct effect.
Keywords: 330